Roles, Responsibilities and Ethics in Neonatal End-of-Life Decisions A Critical Review - Garrett, Mae (2012)
Background- Decisions to limit life-sustaining treatment on the neonatal intensive care unit are both ethically complex and emotionally challenging. As non-autonomous beings, neonates require others to make critical decisions on their behalf. The UK now uses the best-interests standard as a framework for making decisions. There is some confusion as to the specific roles and responsibilities of parents, doctors and nurses in the decision-making process. Aim- This study aims to explore and promote the involvement of parents and nurses in the critical decision-making process. Method- This study uses a critical review methodology. Summary of Findings- The dominant ethical principle used in UK medical law is the best-interests standard which uses the perceived best-interests of the infant to inform decisions. This approach has been adapted for informal use on the NICU to include consideration for parental wishes and concerns. Parents express a desire to be involved in the decision-making process though they do not necessarily wish to take full responsibility for the decision. Neonatal nurses are the chief providers of practical care and emotional support for infant and family in NIC. Nurses currently play only a nominal role in making the decisions which direct the care they provide despite voicing the need for nurse participation. Conclusion- The burden of responsibility is too much for any one person and a mutual approach to decision-making is considered to be the most effective in determining the infant’s best-interests remain at the heart of these decisions. Parents and nurses have valuable contributions to make to the critical decision-making process and the involvement of these parties must be shifted from nominal to influential.